Determining water status of walnut orchards using the crop water stress index and canopy temperature measurements - Lian Mao; Sen Lu; Linqi Liu; Zhipeng Li; Baoqing Wang; Dong Pei; Yongchao Bai (Plant Methods)
Abstract Background Accurately evaluating the water status of walnuts in different growth stages is fundamental to implementing deficit irrigation strategies and improving the yield of walnuts. The crop water stress index (CWSI) based on the canopy temperature is one of the most commonly used tools for current research on plant water monitoring. However, the suitability and effectiveness of using the CWSI as an indicator of the walnut water status under field conditions are still unclear. This paper focuses on walnut orchards in Northwest China using synchronous monitoring of the canopy temperature, meteorological parameters, and water physiological parameters of walnut trees under both full irrigation and deficit irrigation treatments. The aim is to test the effectiveness of the simplified crop water stress index (CWSIs) and the theoretical crop water stress index (CWSIt) in tracking the diurnal and daily variations of the water conditions in walnut orchards. Results The CWSIs can reflect the diurnal and daily changes in the water status of walnut orchards. It was found that the CWSIs at 12:00 local time had the best performance in tracking the daily changes in the water status. Compared to the daily averaged CWSI calculated using the measured transpiration (CWSITr_day), the correlation coefficient, index of agreement, and root mean squared error between the CWSIs and CWSITr_day were 0.82, 0.94, and 0.11, respectively. However, due to the calculation errors of the aerodynamic resistance in walnut trees, the CWSIt was unable to track the diurnal variations in the water status in walnut orchards and the degree of water stress was underestimated. In addition, the variations in minimum canopy resistance in the various growth stages of walnut orchards may also affect the accuracy of the CWSIt in terms of indicating the seasonal changes in the water status. Conclusions The CWSIs provides a non-destructive, quickly and effective method for monitoring the water status of walnuts. However, the results of this study suggest that the effects of aerodynamic resistance parameterization and variations in minimum canopy resistance in the various growth stages of walnut orchards in the CWSIt calculation should be noted.